2015
DOI: 10.1088/0004-637x/811/2/113
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the 3d Structure of the Old Galactic Bulge From the Ogle Rr Lyrae Stars

Abstract: We have analyzed a sample of 27,258 fundamental-mode RR Lyrae variable stars (type RRab) detected recently toward the Galactic bulge by the Optical Gravitational Lensing Experiment (OGLE) survey. The data support our earlier claim that these metal-poor stars trace closely the barred structure formed of intermediate-age red clump giants. The distance to the Galactic center (GC) inferred from the bulge RR Lyrae stars is R 0 = 8.27 ± 0.01(stat) ± 0.40(sys) kpc. We show that their spatial distribution has the shap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
228
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(267 citation statements)
references
References 58 publications
31
228
2
1
Order By: Relevance
“…Although it has a halo-like orbit, it may well be that the majority of bulge RR Lyrae stars reside in an inner halo (e.g., Minniti et al 1999;Kunder & Chaboyer 2008). This is also suggested by their spatial distribution (Dékány et al 2013; although see also Pietrukowicz et al 2015). A larger sample of spectroscopically well-studied bulge RR Lyrae stars and a larger sample of bulge RR Lyrae stars with space velocities is needed to address the uniqueness of this star.…”
Section: Chemical Inferences On the Birthplace Of M176mentioning
confidence: 96%
See 1 more Smart Citation
“…Although it has a halo-like orbit, it may well be that the majority of bulge RR Lyrae stars reside in an inner halo (e.g., Minniti et al 1999;Kunder & Chaboyer 2008). This is also suggested by their spatial distribution (Dékány et al 2013; although see also Pietrukowicz et al 2015). A larger sample of spectroscopically well-studied bulge RR Lyrae stars and a larger sample of bulge RR Lyrae stars with space velocities is needed to address the uniqueness of this star.…”
Section: Chemical Inferences On the Birthplace Of M176mentioning
confidence: 96%
“…In addition to this, the earlier study by Monaco et al (2007) showed that there is a southern and a northern stream that peak around Last, we consider that m176 is a normal RR Lyrae star located toward the direction of the bulge, which is on the tail of the RR Lyrae star velocity distribution. Its spectroscopic [Fe/H] is expected for a RR Lyrae stars located toward the bulge (e.g., Walker & Terndrup 1991;Pietrukowicz et al 2015), as is its distance from the Galactic center. Although it has a halo-like orbit, it may well be that the majority of bulge RR Lyrae stars reside in an inner halo (e.g., Minniti et al 1999;Kunder & Chaboyer 2008).…”
Section: Chemical Inferences On the Birthplace Of M176mentioning
confidence: 99%
“…Jang & Lee (2015) and Joo & Lee (2013) for the details of our model construction. Recent metallicity measurements of bulge RR Lyrae stars show sharply peaked metallicity distribution with an average [Fe/H] in the range of -1.25 to -1.03, depending on the method and metallicity scale (Walker & Terndrup 1991;Kunder & Chaboyer 2008;Pietrukowicz et al 2015). In our modeling, we therefore adopt [Fe/H] = -1.1 for the RR ab stars in the bulge.…”
Section: Two Populations Of Rr Lyrae Stars In the Bulgementioning
confidence: 99%
“…In the observed diagram, I band amplitude was used instead of log T eff , but since there is a good correlation between amplitude and temperature among RR Lyrae stars, our models can be compared with the observation. Four tick marks are added in panel (c) of Figure 3 to provide rough estimates of I-band amplitudes at different temperatures, which were calculated from the maximum points on the empirical relation between the I-band amplitude and log P of bulge RR ab stars ( Figure 15 of Pietrukowicz et al 2015), together with a small shift in amplitude (-0.11) to match the observed value at the fundamental blue edge.…”
Section: Two Populations Of Rr Lyrae Stars In the Bulgementioning
confidence: 99%
See 1 more Smart Citation